Influence of land use and host species on parasite richness, prevalence and co-infection patterns. Issue 1 (January 2021) - Reis, S.; Melo, M.; Covas, R.; Doutrelant, C.; Pereira, H.; Lima, R. de; Loiseau, C.
Graphical abstract: Highlights: Human land use affects blood parasite diversity, prevalence and intra-host parasite interactions. Plasmodium and Haemoproteus parasites are more abundant in degraded habitats. Leucocytozoon parasites are preferentially found in natural forested areas. We found large variations in parasite diversity and prevalence among bird species. Abstract: Tropical forests are experiencing increasing impacts from a multitude of anthropogenic activities such as logging and conversion to agricultural use. These perturbations are expected to have strong impacts on ecological interactions and on the transmission dynamics of infectious diseases. To date, no clear picture of the effects of deforestation on vector-borne disease transmission has emerged. This is associated with the challenge of studying complex systems where many vertebrate hosts and vectors co-exist. To overcome this problem, we focused on an innately simplified system – a small oceanic island (São Tomé, Gulf of Guinea). We analyzed the impacts of human land-use on host-parasite interactions by sampling the bird community (1735 samples from 30 species) in natural and anthropogenic land use at different elevations, and screened individuals for haemosporidian parasites from three genera ( Plasmodium, Haemoproteus, Leucocytozoon ). Overall, Plasmodium had the highest richness but the lowest prevalence, while Leucocytozoon diversity was the lowest despite having the highest prevalence. Interestingly, co-infections (i.e. intra-host diversity) involved primarily Leucocytozoon lineages (95%). We also found marked differences between bird species and habitats. Some bird species showed low prevalence but harbored high diversity of parasites, while others showed high prevalence but were infected with fewer lineages. These infection dynamics are most likely driven by host specificity of parasites and intrinsic characteristics of hosts. In addition, Plasmodium was more abundant in disturbed habitats and at lower elevations, while Leucocytozoon was more prevalent in forest areas and at higher elevations. These results likely reflect the ecological requirements of their vectors: mosquitoes and black flies, respectively.